2017
DOI: 10.1080/09500340.2017.1404655
|View full text |Cite
|
Sign up to set email alerts
|

Bose-Einstein condensation of photons from the thermodynamic limit to small photon numbers

Abstract: Photons can come to thermal equilibrium at room temperature by scattering multiple times from a fluorescent dye. By confining the light and dye in a microcavity, a minimum energy is set and the photons can then show Bose-Einstein condensation. We present here the physical principles underlying photon thermalization and condensation, and review the literature on the subject. We then explore the 'small' regime where very few photons are needed for condensation. We compare thermal equilibrium results to a rate-eq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 90 publications
0
16
0
Order By: Relevance
“…Experimental observations of photon BEC in the microcavity have been reported in [23]. Further studies of the photon BEC based on variations of the previous ideas can be found in [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 92%
“…Experimental observations of photon BEC in the microcavity have been reported in [23]. Further studies of the photon BEC based on variations of the previous ideas can be found in [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 92%
“…These particles possess a mass w = ( ) m n c cutoff 0 2 , where the cavity-cutoff frequency is denoted by ω cutoff and the light velocity in the dye solution is c/n 0 . Furthermore, these particles are trapped in a harmonic potential with frequency W = ( ) c L R n 2 0 0 , that is determined by the cavity length L 0 and the radius of curvature R of the mirror [6,13,29]. Thus, the evolution of the condensate wave function y ( ) t r, , i.e.the electric field normalised to the photon number, is described by an opendissipative Schrödinger equation of the form [23, 29-31] Figure 1.…”
Section: Modelmentioning
confidence: 99%
“…A coherent coupling between a laser-driven optomechanical membrane and a Bose-Einstein condensate has been achieved as well [30,31] which shows strong squeezing in the mechanical mode [31]. The optical cavity has been used to demonstrate variable potentials leading to a small critical photon number of N 0 = 68 for condensation [32] which physical principles are discussed in [33].…”
Section: Introductionmentioning
confidence: 99%